(untitled) (Heritage, 2025)
SUMMARY This research was initiated with the aim of opening up new possibilities in the interpretation of the poem „Flute” („Flute”, 1858) by Konstantin Miladinov and thus making a contribution to the study of the poetics and aesthetics of the first Macedonian poet. Our primary task in this paper is to show that "beneath" the traditionally understood meaning of the text (longing for one’s homeland abroad), there is another deeper, archetypal layer that illuminates some new paths in interpretation for the attentive reader. The central motif of the song - the flute - is interpreted in a magical-mythological key, while pointing out certain similarities with Nastasijevi’s concept of the native melody preserved in the words and tones of the folk language, song, and music.